1994
DOI: 10.1136/bmj.308.6937.1125
|View full text |Cite
|
Sign up to set email alerts
|

Widening inequality of health in northern England, 1981-91

Abstract: Objective-To identify relative and absolute changes in mortality in the Northern region of England between 1981 and 1991. Design-1981 and The decline in the relative position of the poorest areas was particularly great, and there was no narrowing ofinequalities across the remainder ofthe socioeconomic spectrum. In absolute terms, there were improvements in mortality in all age categories in the most affluent areas. In the poorest areas improvements in the 55-64 age group were balanced by increased mortality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
199
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 325 publications
(204 citation statements)
references
References 14 publications
(7 reference statements)
4
199
0
1
Order By: Relevance
“…The answer is a guarded 'no'. This study has demonstrated increases in the geographical disparities in health status that were not due to migration and therefore confirmed the overall conclusions of previous studies within England and Wales of widening inequalities in health during the 1990s (Dorling et al, 2001;McLoone & Boddy, 1994;Phillimore et al, 1994;Shaw et al, 2005). However, it is clear that selective migration makes an important contribution to these increases, so we believe the current methodology for assessing changes in inequalities should not be used in isolation, as an indication of the magnitude of these changes or for assessing the success or otherwise of policies to reduces health inequalities.…”
Section: Most Affluent Decilessupporting
confidence: 90%
See 3 more Smart Citations
“…The answer is a guarded 'no'. This study has demonstrated increases in the geographical disparities in health status that were not due to migration and therefore confirmed the overall conclusions of previous studies within England and Wales of widening inequalities in health during the 1990s (Dorling et al, 2001;McLoone & Boddy, 1994;Phillimore et al, 1994;Shaw et al, 2005). However, it is clear that selective migration makes an important contribution to these increases, so we believe the current methodology for assessing changes in inequalities should not be used in isolation, as an indication of the magnitude of these changes or for assessing the success or otherwise of policies to reduces health inequalities.…”
Section: Most Affluent Decilessupporting
confidence: 90%
“…We have concentrated on mortality as this has been the outcome measure in most papers relating to widening health inequalities (Dorling, 1997;Dorling et al, 2001;McLoone & Boddy, 1994;Phillimore et al, 1994;Shaw et al, 2005) and used a 10-year period as this is the usual period of comparison.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 1991 Census is the first decennial census to provide information on ethnicity [17]. The latter four parameters were used to calculate the Townsend score, a measure of socioeconomic status with high indices indicating lower socioeconomic status [18]. Area-based population densities were calculated for children (0-16 years old) by dividing the respective populations in each ED by the area in hectares.…”
Section: Population Census Data Data From the 1991 Census (The 1991mentioning
confidence: 99%